New limits on doubly charged bileptons from CERN LEP data and the search at future electron-positron and electron-photon colliders - Gregores, E. M. [UNESP]; Gusso, A. [UNESP]; Novaes, Sérgio Ferraz [UNESP] (American Physical Society (APS), 2001)
We show that the accumulated CERN LEP-II data taken at √s = 130-206 GeV can establish more restrictive bounds on doubly charged bilepton couplings and masses than any other experiment so far. We also analyze the discovery potential of a prospective linear collider operating in both e+e- and e γ modes.
Keywords: atomic particle; calculation; electron; mass; model; photon; physics; polarization; positron